Multilayer analysis of supply chain strategies' impact on sustainability. Issue 2 (March 2020) - López, Cristina; Ruiz-Benítez, Rocío
Abstract: Integrating lean, green and resilient strategies into Supply Chain (SC) decisions is a key success factor for transformation toward sustainability. These strategies are increasingly common in the SC, although their implementation and results are not the same across different SC levels (Tier 1, 2 and 3 suppliers and the focal company). In spite of this, earlier studies have not explored in detail their effects on environmental, economic and social sustainability dimensions nor differentiated between SC levels and therefore implementation strategies overlook the difference between these levels. Accordingly, a novel multilevel analysis of the aerospace manufacturing SC based on Interpretive Structural Modeling (ISM) is carried out. This approach allows exploring the effects of combining lean, green and resilient strategies on specific sustainability performance measures in the aerospace manufacturing SC. The findings reveal differences between SC levels on the effects of lean, green and resilient strategies on the different sustainability dimensions. Additionally, Tiers 2 and 3 show a higher resistance or lower implication in the development of lean, green and resilient strategies than the focal company and Tier 1 companies. Final ISM models become a useful tool for managers to specifically establish coordinated long-term SC sustainability programs for each SC level. Highlights: A novel multilevel analysis of the aerospace manufacturing supply chain is developed. The ISM method has been adapted for multilevel supply chain analysis. Green practices only cause high impact on the environmental dimension in tier 2 and 3. Lean and resilience cause a lower impact on the economic dimension in tier 2 and 3. The social dimension is not highly improved by lean practices in tier 2 and 3.